Roles of mitochondria in modulating chicken innate immunity following newcastle disease virus infection - Mohamad Wali, Haryati Shila (2019)
Mitochondria have been established as having a vital role in innate immunity. Mitochondrial antiviral signalling (MAVS) protein is a mitochondrial protein proven to modulate the production of interferons and pro-inflammatory cytokines as well as initiating apoptosis in viral infection. Newcastle disease (ND) is a common threat to the poultry industry globally with genotype VII Newcastle disease virus (NDV) strains becoming one of the prominent virulent NDV strains. Antiviral innate immune response involve various pattern recognition receptors (PRR) such as Toll-like receptors (TLR), retinoic acid-inducible gene I (RIG-I) and melanoma differentiation-associated protein 5 (MDA5) to identify invading microorganism via their pathogen-associated molecular patterns (PAMP) like double-stranded RNA (dsRNA), bacterial lipopolysaccharide (LPS) and viral proteins. This leads to further downstream processes in the signalling cascade of the innate immune system. In this study, CARD adaptor inducing IFN-β (CARDIF), a prominent mitochondrial adaptor molecule linking RIG-I and MDA5 is amplified and exogenously expressed in two chicken cell lines prior to IBS002/11 strain (genotype VII NDV) infection. The gene expression experiment was conducted to assess whether the presence of CARDIF affected the production of type I interferons and proinflammatory cytokines in both cell lines following NDV strain IBS002/11 infection, besides its role in the induction of apoptosis. The contribution of mitochondrial DNA (mtDNA) in chicken innate immunity was also assessed following NDV infection. The assessments of cytokines expressions and mtDNA level were conducted via qPCR assay, while the determination of cell proliferation and apoptosis were conducted via MTS and JC-1 assays. Morphological evaluation was conducted by transmission electron micrography (TEM). All experiments were carried out on two cells lines; DF-1 and HD- 11. The DF-1 cell line is a spontaneously transformed chicken embryo fibroblast while HD-11 is a chicken macrophage-like cell line. The CARDIF gene was successfully amplified via PCR and cloned into the pcDNA6V5-His B plasmid, a mammalian expression vector to produce the plasmid pcDNA6/CARDIF. Meanwhile, two truncated genes of the original CARDIF gene were also amplified and cloned into the expression vector yielding pcDNA6/ΔCARD (putative CARDIF lacking the CARD domain) and pcDNA6/ΔTM (putative CARDIF lacking the TM domain). The effects of exogenous expression of CARDIF on the production of type I and II IFNs and pro-inflammatory cytokines in both cell lines following NDV infection were conducted via quantitative polymerase chain reaction (qPCR). Despite upregulated levels of type I IFN (IFN-α and IFN-β) following NDV infection observed in both cell lines as the effect of exogenous expression of CARDIF, the expression of IFN-α occurred at a much later time point (72 h) in both cell lines, showing that the production of IFN-α was less affected by the presence of the CARDIF gene in comparison to IFN-β. HD-11 cells exhibited a greater magnitude of IFN-β upregulation compared to DF-1 cells. The transfected CARDIF gene also upregulated the expression of IFN-γ (type II IFN) as well as IL-18 in HD-11 cells while the same molecules were downregulated in DF-1 cells. CXCLi2, a chemokine was upregulated in both cell lines while IL-1β was found to be upregulated in DF-1 cells. The presence of CARDIF resulted in the decreased number of viral copies over the treatment period in contrast to both truncated CARDIF genes. Both truncated genes caused an increase in the viral copy number over the treatment period. Subsequently, the mtDNA levels were detected to be higher (P<0.05) in infected cells compared to the control. Two mtDNA genes were used in the qPCR assay i.e. Cyt b and COIII whereby the higher level of mtDNA expression in infected cells means leakage of the mtDNA into the cytosol. In this study, the leakage of mtDNA to the surroundings assisted in triggering the production of pro-inflammatory cytokines as well as type I IFN. The proliferation percentage of the cells was assessed via the MTS assay in two conducts, the conventional and co-treatment method. A continuous decline of HD-11 cells in contrast to the DF-1 cells in the existence of the CARDIF gene was observed with the co-treatment method considered as a better approach in determining the percentage of cell proliferation following virulent NDV infection. The occurrence of CARDIF gene also initiated the onset of apoptosis as a measure to curb viral infection. The assessment was conducted via the mitochondrial membrane potential (Δψ) assay (JC-1 assay). The results of JC-1 assay supported those of the MTS assay whereby the decline of cell proliferation percentage in the MTS assay is in agreement with the increased percentage of apoptotic cells in the JC-1 assay. The results of the cell proliferation and mitochondrial membrane potential assays were further confirmed by visual assessment of the cell morphology in TEM. Noticeable hallmarks of apoptosis such as convolution of nuclear membrane, condensed chromatin and the presence of lipid droplets were identified in both cell lines. Therefore, this study concluded that the presence of CARDIF, a mitochondrial adaptor molecule managed to prompt the production of type I and type II IFNs, as well other proinflammatory cytokines during infection with virulent NDV strain. The presence of the exogenous gene also showed better impact on the cell component of the immune system (HD-11 cells) compared to the stromal cell line (DF-1 cells). The exogenous gene managed to induce apoptosis in both cell lines, with HD-11 cells being more susceptible following NDV infection.